2002
DOI: 10.1177/105268460201200205
|View full text |Cite
|
Sign up to set email alerts
|

School Leaders and Antiracism: Overcoming Pedagogical and Political Obstacles

Abstract: In this study school principals acknowledged the manifestations of racism within their schools, but their lack of conceptual clarity led to ambivalence and ambiguities in their practice of antiracism pedagogy. Stakeholders, such as teachers who resisted staff antiracism development initiatives and white parents who withdrew from racially diverse learning environments, further complicated this shortcoming. Principals’ limited conceptual knowledge of antiracism combined with the desire to maintain a culture of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 18 publications
1
48
0
2
Order By: Relevance
“…Consistent with other research (McMahon & Armstrong, 2010;Ryan, 2012;Solomon, 2002), this study found that democracy in education existed in isolated acts by individual educators. Several of the interviewees spoke of themselves as role models for their teaching faculty.…”
Section: Factors That Facilitate And/or Hinder Democratic Goals Of Edsupporting
confidence: 91%
“…Consistent with other research (McMahon & Armstrong, 2010;Ryan, 2012;Solomon, 2002), this study found that democracy in education existed in isolated acts by individual educators. Several of the interviewees spoke of themselves as role models for their teaching faculty.…”
Section: Factors That Facilitate And/or Hinder Democratic Goals Of Edsupporting
confidence: 91%
“…Many authors offered specific skills that school principals must be taught though nearly all were couched in what school leaders should be able to do, and not in what university faculty should prepare principals to be able to do. Solomon (2002) believes that school leaders should know how to do the following, all related to anti-racist work:…”
Section: Preparing Leaders For Social Justicementioning
confidence: 99%
“…A recurring theme from these schools and from the literature on school change is that exemplary leadership helps point to the necessity for change and helps make the realities of change happen (Bell, Jones, & Johnson, 2002;Blackmore, 2002;Bogotch, 2002;Fullan, 1993;Goldfarb & Grinberg, 2002;Grogan, 2002aGrogan, , 2002bLyman & Villani, 2002;Rapp, 2002;Riester et al, 2002;Solomon, 2002). A recurring theme from these schools and from the literature on school change is that exemplary leadership helps point to the necessity for change and helps make the realities of change happen (Bell, Jones, & Johnson, 2002;Blackmore, 2002;Bogotch, 2002;Fullan, 1993;Goldfarb & Grinberg, 2002;Grogan, 2002aGrogan, , 2002bLyman & Villani, 2002;Rapp, 2002;Riester et al, 2002;Solomon, 2002).…”
mentioning
confidence: 99%